Development of marketing strategies in the digital era to increase sales in Klaten, Central Java (Case study of PT Panma Metal Agung Sejahtera) - Arahmah, Melina; Hardjomidjojo, Hartrisari; Raharja, Sapta (Keynesia : International Journal of Economy and Business, 2025)
Marketing strategy plays a crucial role in enhancing the competitiveness of micro, small, and medium enterprises (MSMEs) in the digital era, including PT Panma Metal Agung Sejahtera, which faces challenges in optimizing the use of digital media. The phenomenon observed is that although revenue has increased since adopting digital platforms, the strategies applied have not yet significantly driven sustainable sales growth. This study aims to analyze the application of the Business Model Canvas (BMC) and SWOT analysis, determine strategic priorities using the Analytic Hierarchy Process (AHP), and evaluate the effectiveness of digital platforms in supporting marketing activities. The research method employed a qualitative approach, supported by SWOT analysis, BMC, AHP, and the use of Manual Data Analysis Procedure (MDAP) and Coding Color Analysis Procedure (CCAP). The findings reveal that the dominant factors in marketing strategy are strengthening digital systems and human resources, with priority strategies focusing on the development of an integrated website with marketplace features and the utilization of social media for promotion. The study concludes that the integration of BMC, SWOT, and AHP produces more adaptive and measurable strategies, while the effective use of digital platforms enhances marketing performance and expands the market reach of PT Panma Metal Agung Sejahtera.